Community and identity in nineteenth century Montreal: The founding of Saint Patrick's Church. - Leitch, Gillian Irene. (University of Ottawa (Canada), 1999)
In 1817 Montreal's Catholic Church, under the direction of the Seminary of Saint Sulpice, granted English-language services to its Irish congregation. From that time on, the Irish of Montreal enjoyed services separate from the French Canadians. This separation was emphasized with the opening of Saint Patrick's Church in 1847, purpose-built for the Irish Catholics of Montreal. This thirty year period, understudied in relation to the city's Irish population, marks the time when the Irish of Montreal became a community, forging its identity within and without the Catholic Church. This identity was developed outside the Catholic Church through social organizations that attracted the ethnic Irish exclusively, such as the Hibernian Benevolent and Saint Patrick Societies, founded during this period. Cultural celebrations, notably those surrounding Saint Patrick's Day, were occasions where the community could share their traditions and celebrate their Irish heritage. These secular activities were not organized by the Roman Catholic Church in Montreal, but the Church was very involved. The Saint Patrick's Society included the clergy within its executive, while the cathedral of Notre Dame hosted the multi-denominational service held in honour of Saint Patrick. The interaction of the Irish Catholics and the Catholic Church is the primary focus of this thesis, as the community expressed itself within the institution often. (Abstract shortened by UMI.)
Keywords: History, Church.